2007
DOI: 10.1271/bbb.70174
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Epigallocatechin Gallate Elevates Levels of Circulating Adiponectin in Non-Obese Type-2 Diabetic Goto-Kakizaki Rats

Abstract: Epigallocatechin gallate (EGCG) reportedly enhances plasma adiponectin levels in models of insulin resistance and obesity. In this study, we found that EGCG increases plasma adiponectin levels and decreases plasma triacylglycerol levels in non-obese diabetic Goto-Kakizaki rats with insulin secretory dysfunction. These results suggest that EGCG ameliorates lipid metabolic abnormality even in non-obese rats, probably by increasing adiponectin production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…EGCG has a protective action against several deleterious effects of diseases by minimizing OS (Katiyar et al, 2001;Tipoe et al, 2010;Yao et al, 2008). Dietary supplementation with EGCG was suggested to potentially contribute to T2DM prevention and treatment (Shimada et al, 2007;Wolfram et al, 2006). Results from this study prove that WTEA is rich in EGCG.…”
Section: Discussionmentioning
confidence: 54%
“…EGCG has a protective action against several deleterious effects of diseases by minimizing OS (Katiyar et al, 2001;Tipoe et al, 2010;Yao et al, 2008). Dietary supplementation with EGCG was suggested to potentially contribute to T2DM prevention and treatment (Shimada et al, 2007;Wolfram et al, 2006). Results from this study prove that WTEA is rich in EGCG.…”
Section: Discussionmentioning
confidence: 54%
“…Based on these data, adiponectin was conceived to be a novel therapy target for obese and insulin resistance [21]. Elevation of adiponectin level by EGCG was documented in non-obese spontaneous diabetic rats and spontaneous hypertension rats [22], [23]. Based on the above research, we hypothesized that GTPs might regulate the adiponectin levels in HF fed rats, through which GTPs exert their preventive effects on obesity and related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that certain �avonoids exhibit hypoglycemic activity and pancreas beta cell regeneration ability. us the signi�cant anti-diabetic effect of BME and LME may be due to the presence of more than one antihyperglycemic principle and their synergic properties [40,41]. It was also observed that among the extracts tested the methanolic extract of the bark and leaves was the most effective.…”
Section: Discussionmentioning
confidence: 95%